From silence to dialogue: addressing gender inequalities in the livestock sector on local tv - Njiru, Nelly; Kiptum, B.; Galiè, Alessandra (International Livestock Research Institute, 2025)
The Kenya Broadcasting Corporation (KBC) TV Biz Check program aired a discussion with a researcher from the International Livestock Research Institute (ILRI), Nairobi on 24 September 2025 that focused on gender inequalities in the livestock sector and some of the transformative efforts being implemented by gender researchers from ILRI in different countries, in Africa, and East and South Asia. The KBC Business channel has about 12.2 thousand subscribers and is accessible through various media: Twitter; Facebook; and KBC official website and YouTube. The televised discussion spotlighted gender inequality as a public issue requiring attention. The aired discussion linked restrictive gender norms to outcomes in livelihoods, care work, and wellbeing fostering public awareness and normative change.